2006
DOI: 10.1038/sj.onc.1209740
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin modulates phosphorylation, signaling and trafficking of epidermal growth factor receptor in human T47D breast cancer cells

Abstract: Prolactin (PRL) is a polypeptide hormone produced by the anterior pituitary gland and other sites that acts both systemically and locally to cause lactation and other biological effects by interacting with the PRL receptor, a Janus kinase (JAK)2-coupled cytokine receptor family member, and activating downstream signal pathways. Recent evidence suggests PRL is a player in the pathogenesis and progression of breast cancer. Epidermal growth factor (EGF) also has effects on breast tissue, working through its recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 98 publications
(156 reference statements)
5
64
1
Order By: Relevance
“…Thus, the degree and kinetics of EGFR activity and downregulation are believed to be critical modulators of EGF actions. We previously uncovered that, in addition to tyrosine phosphorylation, EGFR also undergoes threonine phosphorylation in response to EGF, which is ERK activation dependent and can slow the pace of ligand-induced receptor downregulation (Huang et al, 2003(Huang et al, , 2006Li et al, 2008). In this study, we found that blockade of the ERK pathway, but not of the Akt pathway, eliminates EGF-induced EGFR threonine phosphorylation, which in turn potentiates receptor tyrosine phosphorylation (activation) and subsequently enhances EGFR endocytic downregulation in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Thus, the degree and kinetics of EGFR activity and downregulation are believed to be critical modulators of EGF actions. We previously uncovered that, in addition to tyrosine phosphorylation, EGFR also undergoes threonine phosphorylation in response to EGF, which is ERK activation dependent and can slow the pace of ligand-induced receptor downregulation (Huang et al, 2003(Huang et al, , 2006Li et al, 2008). In this study, we found that blockade of the ERK pathway, but not of the Akt pathway, eliminates EGF-induced EGFR threonine phosphorylation, which in turn potentiates receptor tyrosine phosphorylation (activation) and subsequently enhances EGFR endocytic downregulation in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…Cell starvation, inhibitor treatment, stimulation, protein extraction, immunoprecipitation, immunoblotting and densitometry These procedures were performed as previously described (Huang et al, 2003(Huang et al, , 2006Ma et al, 2009). For experiments in which ubiquitination was assayed, N-ethylmaleimide (5 mM) was added to the lysis buffer to prevent post-lysis deubiquitination of proteins (Deng et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations